Intestinal Tumor in a Dish - Ohta, Yuki; Sato, Toshiro (Frontiers in Medicine, 2014)
Predicting the response of colorectal cancer tumors to novel chemotherapeutic agents is significantly complicated by their underlying genetic and epigenetic diversity. Large-scale clinical trials involving thousands of patients are often necessary in order to accurately determine efficacy during drug development. Recent advances in genetic sequencing has allowed us to improve the prediction of drug response through genetic stratification of patients into smaller populations, yet the complexity of the cancer genome still often confounds accuracy of drug response prediction. Ultimately, we may need to replicate patient’s own tumor in a dish in order to test drug responses so that the optimal treatment can be identified. We recently developed highly efficient and tractable organoid culture system for intestinal stem cells, in which single stem cells form 3D structures recapitulating original tissue architecture. This technology has also been applied to colorectal tumors and enables us to monitor the growth and response of the patient’s own tumors. In this review, we provide an overview focusing on colorectal cancer organoid culture and its perspective for clinical applications.